Manta and devil ray aggregations: conservation challenges and developments in the field - Palacios, Marta D.; Stewart, Joshua D.; Croll, Donald A.; Cronin, Melissa R.; Trejo-Ramírez, Abel; Stevens, Guy M. W.; Lezama-Ochoa, Nerea; Zilliacus, Kelly M.; González−Armas, Rogelio; Notarbartolo di Sciara, Giuseppe; Galván−Magaña, Felipe (Frontiers in Marine Science, 2023)
Manta and devil rays (mobulids) are filter feeding elasmobranchs with extreme K-selective life histories found circumglobally from temperate to tropical waters. Their vulnerability to fisheries exploitation, bycatch, boat collisions, entanglement and unregulated tourism is exacerbated by their aggregative behavior. Studies have identified aggregation sites around the world for all nine mobulid species, with these groupings varying from a few individuals to thousands. However, the terminology used to define these aggregations and the drivers underpinning them remain unclear, hindering the development of effective management and conservation strategies. Here, we analyze aggregation behavior for mobulid species, providing consistent definitions for grouping events and summarizing the existing research on drivers and environmental factors triggering these events. We find that aggregation behaviors facilitate socializing and key life history functions in mobulids, including feeding, courtship and mating, predation avoidance, cleaning, and thermoregulation. Conservation threats and management mitigation opportunities associated with aggregations sites include fisheries, tourism, spatial protection, and climate change. Finally, we highlight knowledge gaps for future research prioritization and developments in the field for the identification of aggregation sites, the study of aggregation size and demographics and the functions and timing of aggregations.